Large Pleural Effusion: A Pitfall in the Quantitation of 99mTc-PYP Imaging for ATTR Cardiac Amyloidosis. (6th September 2022) - Khatri, Wajahat; Polydefkis, Michael; Vaishnav, Joban; Saad, Elie; Solnes, Lilja B.; Rowe, Steven P.
Abstract: Transthyretin cardiac amyloidosis (ATTR and ATTRv) is an underrecognized cause of heart failure that results from myocardial deposition of misfolded protein (TTR or prealbumin). The diagnosis can be confirmed by uptake of 99m Tc-pyrophosphate ( 99m Tc-PYP) in the heart with serologic studies to rule out light chain disease. We present the case of a 70-year-old woman who underwent a 99m Tc-PYP scan. The patient had a large right-sided pleural effusion that lowered counts in the right chest on planar imaging, interfered with ratio-based grading of PYP uptake, and highlighted the importance of obtaining SPECT/CT for problem-solving in cases where uptake ratios may be spurious.